2007
DOI: 10.1080/02607470701603209
|View full text |Cite
|
Sign up to set email alerts
|

Researching class in the classroom: addressing the social class attainment gap in Initial Teacher Education

Abstract: IntroductionThis paper focuses on a small group of student teachers who volunteered to participate in a research project on the achievement of working class pupils. Alongside the exploration of the substantive issues within schools and classrooms, a key purpose of this initiative was to inform programme development in Initial Teacher Education (ITE). In this paper we focus on the student teachers themselves and on how their involvement in the project shaped their understandings of both social class and underac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Arguably, deficit perspectives of working-class children have always been a feature of English education. Recently, however, a number of authors have pointed to the lack a developed and critical consciousness of social class that might provide a starting point from which teachers could challenge this position (Allard and Santoro 2006;Gazeley and Dunne 2007). Lupton and Thrupp (2011) highlight the sympathetic but individualised accounts that headteachers produce to account for the adverse social and economic circumstances encountered by families in disadvantaged schools.…”
Section: Constraints On Pedagogical Practice In Working-class Schoolsmentioning
confidence: 97%
“…Arguably, deficit perspectives of working-class children have always been a feature of English education. Recently, however, a number of authors have pointed to the lack a developed and critical consciousness of social class that might provide a starting point from which teachers could challenge this position (Allard and Santoro 2006;Gazeley and Dunne 2007). Lupton and Thrupp (2011) highlight the sympathetic but individualised accounts that headteachers produce to account for the adverse social and economic circumstances encountered by families in disadvantaged schools.…”
Section: Constraints On Pedagogical Practice In Working-class Schoolsmentioning
confidence: 97%
“…For teaching institutions and in other contexts where professor/student research collaborations are not possible, teacher educators might consider incorporating student-directed research projects on topics in multicultural education as an additional approach that complements more traditional school, community-based, and other forms of extended learning. Our work builds on existing literature demonstrating the secondary benefits of student research in teacher education for equity (Gazeley & Dunne, 2007;Rubin et al, 2016) and asserts that engaging students as coresearchers has fundamental value for prospective teachers' personal, academic, and professional engagement with critical multicultural education. In this way, we believe that mentored undergraduate research experiences facilitate critical goals in multicultural teacher education and have the potential to create more caring, critical and competent educators.…”
Section: Discussionmentioning
confidence: 77%
“…As a result of facilitating this school-based research, preservice teachers developed a more critical, structural analysis of racial and economic oppression and commitment to addressing these issues in their future classrooms (p. 434). Gazeley and Dunne (2007) also reported on a study where preservice teachers were encouraged to research the impact of social class in secondary schools where they were working as student teachers. The project involved(a) providing the undergraduates with related reading and training on collecting qualitative data in schools,(b) having the preservice teachers conduct individual interviews and focus groups with school leaders, teachers and students, and(c) supporting the preservice teachers in writing up their research findings.…”
Section: Extended Learning Through Undergraduate Researchmentioning
confidence: 99%
“…Indeed, qualitative research by the Sutton Trust has suggested that ‘some primary school teachers do not think that grammar schools are suitable for children from poorer families' and that some lower‐income parents ‘might prefer a more “rounded” education for their child' (Sutton Trust, ). Teachers' low expectations for certain pupils may even be inadvertently discouraging working‐class pupils from applying, creating a self‐fulfilling prophecy (Gazeley & Dunne, ).…”
Section: Conceptual Framework: What Mechanisms Might Drive the Relatimentioning
confidence: 99%